"Synthesis, design and characterization of supramolecular self-assembly of calix[4]resorcinare substituted LCs". (13th June 2018) - Gajjar, Jinal; Vekariya, Rajesh H.; Sharma, Vinay S.; Parekh, Hitesh
Abstract: A new class of supramolecular calix[4 ]resorcinarene substituted alkoxy side chain (-OC5 H11, -OC8 H17, -OC10 H21 ) has been synthesized and well characterized. These supramolecular compounds were investigated by polarizing optical microscope (POM), differential scanning calorimetry (DSC), thermogravimmetric analysis (TGA) and high-temperature X-ray diffraction studies (XRD). The present synthesized supramolecular derivatives are promising to stabilize the hexagonal columnar phase over a broad thermal range. All the synthesized derivatives showed hexagonal columnar phase at lower temperature and showed enantiotropical nature. Compound2a with small alkyl spacer on eight side showed higher thermal stability as compare to higher alkyl spacer substituted compounds2b and compound2c . These research results suggest that calix[4 ]resorcinarene was a good platform to construct bowl-shaped derivatives to exhibits the columnar liquid crystal phase and the observed liquid crystalline properties were greatly effected by the substituted alkoxy side chain on eight side of calix[4 ]resorcinarene skeletone. All the synthesized compounds were characterized by FT-IR, 1 H NMR and 13 C NMR spectroscopy. Graphical Abstract: